An austenitic stainless steel, a method for producing the same and use thereof

CN121992312BActive Publication Date: 2026-10-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511921966.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-10-27
Estimated Expiration
2045-12-18

AI Technical Summary

Technical Problem

但是,随着先进装备对服役寿命要求不断提高,例如,第四代钠冷快堆反应堆的设计寿命由目前的40年提升至60~100年,而现有的奥氏体不锈钢的蠕变断裂强度难以满足长期的服役要求

Benefits of technology

1.一方面,本发明提供一种奥氏体不锈钢,按重量百分比计,所述奥氏体不锈钢的化学成分如下:C≤0.10%,N≤0.12%,Si≤2.0%,Mn:1.0~2.0%,Cr:16.0~18.0%,Ni:10.0~14.0%,Mo:2.0~3.0%,Nb:0.05~0.10%,Ti:0.05~0.10%,S≤0.02%,P:0.04~0.06%,余量为Fe及不可避免的残余元素。需要说明的是,本发明通过增加不锈钢中P的含量,高温下P与空位的交互作用可以降低Cr、Mo等溶质原子的扩散速率,抑制M23C6碳化物等在晶界处的形核,显著降低了析出数量,与此同时,M23C6碳化物粗化过程中向外排P,形成了P元素包裹M23C6碳化物的核壳结果,降低了其粗化速率,进而抑制了蠕变过程中析出相造成的蠕变空洞,提高了蠕变断裂强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121992312B_ABST
    Figure CN121992312B_ABST
Patent Text Reader

Abstract

The application provides an austenitic stainless steel and a preparation method and application thereof, and relates to the field of high-temperature-resistant austenitic stainless steel. The chemical composition of the austenitic stainless steel is as follows in percentage by weight: C is less than or equal to 0.10%, N is less than or equal to 0.12%, Si is less than or equal to 2.0%, Mn is 1.0-2.0%, Cr is 16.0-18.0%, Ni is 10.0-14.0%, Mo is 2.0-3.0%, Nb is 0.05-0.10%, Ti is 0.05-0.10%, S is less than or equal to 0.02%, P is 0.04-0.06%, and the balance is Fe and inevitable residual elements. By increasing the content of P in the stainless steel, the interaction between P and vacancies at high temperature can reduce the diffusion rate of solute atoms such as Cr and Mo, inhibit the nucleation of M 23 C6 carbide and the like at the grain boundary, significantly reduce the number of precipitates, at the same time, M 23 P is discharged outward during the coarsening process of M 23 C6 carbide, reduces the coarsening rate, and further inhibits the creep cavities caused by precipitates in the creep process, and improves the creep fracture strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-temperature resistant austenitic stainless steel technology, specifically relating to an austenitic stainless steel with high creep rupture strength, its preparation method, and its application. Background Technology

[0002] Austenitic stainless steel, due to its excellent cold and hot working properties, corrosion resistance, and mechanical properties, is widely used as a key structural material in petrochemical, nuclear power, and aerospace industries. During long-term service, methyl sulfide (M) will gradually precipitate. 23 Brittle phases such as C6 carbides, σ phase, and Laves phase reduce the high-temperature stability of austenitic stainless steel, leading to phenomena such as decreased impact toughness, reduced creep rupture strength, and increased irradiation swelling rate, thus affecting the material's service life. With technological advancements, the design service life and service temperature of components are continuously increasing, such as reactor internals in fourth-generation nuclear power reactors and high-temperature pyrolysis furnace tubes in the petrochemical industry. Therefore, there is a need to develop new austenitic stainless steels that are resistant to high temperatures and have long service lives.

[0003] Reducing the tendency of phase precipitation during service is key to improving the high-temperature stability of austenitic stainless steel. Existing technologies, such as reducing carbon content, nitrogen alloying, and adding Nb / Ti stabilizing elements, have all reduced the tendency of phase precipitation to some extent and have led to the development of various grades of austenitic stainless steel. However, as advanced equipment demands increasingly longer service lives—for example, the design life of fourth-generation sodium-cooled fast reactors has been increased from the current 40 years to 60-100 years—the creep rupture strength of existing austenitic stainless steels is insufficient to meet the requirements for long-term service. Summary of the Invention

[0004] Therefore, the present invention provides an austenitic stainless steel, its preparation method and application, with the main objective of providing an austenitic stainless steel with high creep rupture strength.

[0005] To address the aforementioned problems, the present invention provides an austenitic stainless steel, wherein the chemical composition of the austenitic stainless steel, by weight percentage, is as follows: C≤0.10%, N≤0.12%, Si≤2.0%, Mn: 1.0~2.0%, Cr: 16.0~18.0%, Ni: 10.0~14.0%, Mo: 2.0~3.0%, Nb: 0.05~0.10%, Ti: 0.05~0.10%, S≤0.02%, P: 0.04~0.06%, with the balance being Fe and unavoidable residual elements.

[0006] Furthermore, the sum of the mass percentages 'a' of C, N, and P in the austenitic stainless steel satisfies the condition: a ≤ 0.15%.

[0007] Furthermore, the mass percentage of C in the austenitic stainless steel is ≤0.05%.

[0008] Furthermore, in the austenitic stainless steel, the sum of the mass percentages of Nb and Ti is b, and the mass percentage of P is c, where b and c satisfy: b / c≤3.

[0009] Furthermore, at room temperature, the mechanical properties of the austenitic stainless steel are: yield strength Rp0.2 ≥ 230 MPa; tensile strength Rm ≥ 540 MPa; elongation A ≥ 50%; impact toughness KV2 ≥ 350 J; and / or At 550℃, the mechanical properties of the austenitic stainless steel are: yield strength Rp0.2 ≥ 116 MPa; tensile strength Rm ≥ 396 MPa; and / or Under conditions of 550℃ and 3000h, the creep rupture strength of the austenitic stainless steel is ≥302MPa; and / or Under conditions of 550℃ and 10000h, the creep rupture strength of the austenitic stainless steel is ≥277MPa; and / or Under conditions of 550℃ and 3000h, the M in the austenitic stainless steel 23 The size of C6 carbides is <200 nm.

[0010] On the other hand, the present invention provides a method for preparing the austenitic stainless steel according to any one of the above claims, comprising the following steps: The raw materials are prepared according to the chemical composition of the austenitic stainless steel, and then melted and cast to obtain a billet. The billet is then subjected to homogenization treatment, heat treatment and solution treatment in sequence to obtain the austenitic stainless steel.

[0011] Furthermore, the solution treatment temperature is 1100~1150℃; the solution treatment holding time is 30~60min.

[0012] Furthermore, the homogenization treatment temperature is 1230~1250℃; the homogenization treatment holding time is ≥20h.

[0013] Furthermore, the hot working process includes sequential forging and rolling processes; Preferably, the initial rolling temperature is 1100~1200℃ and the final rolling temperature is ≥900℃.

[0014] In another aspect, the present invention provides an application of the austenitic stainless steel described in any of the above claims, wherein the austenitic stainless steel is processed into plates, bars or forgings for fourth-generation nuclear power, thermal power or petrochemical applications.

[0015] The austenitic stainless steel, its preparation method, and its application provided by this invention have the following beneficial effects: 1. On one hand, the present invention provides an austenitic stainless steel, wherein the chemical composition of the austenitic stainless steel, by weight percentage, is as follows: C≤0.10%, N≤0.12%, Si≤2.0%, Mn: 1.0~2.0%, Cr: 16.0~18.0%, Ni: 10.0~14.0%, Mo: 2.0~3.0%, Nb: 0.05~0.10%, Ti: 0.05~0.10%, S≤0.02%, P: 0.04~0.06%, with the balance being Fe and unavoidable residual elements. It should be noted that the present invention, by increasing the P content in the stainless steel, can reduce the diffusion rate of solute atoms such as Cr and Mo at high temperatures through the interaction between P and vacancies, thereby inhibiting the diffusion of Mn. 23 Nucleation of C6 carbides and other compounds at grain boundaries significantly reduced the amount of precipitates, while M... 23 During the coarsening process of C6 carbides, P is expelled outwards, forming P-encapsulated M. 23 The core-shell structure of C6 carbides reduces its coarsening rate, thereby suppressing creep cavities caused by precipitated phases during creep and improving creep fracture strength.

[0016] 2. Furthermore, by limiting the C+N+P content to ≤0.15% and the C content to ≤0.05%, the carbon source C is reduced, and the formation of M6C carbides is reduced by avoiding increased lattice distortion from N and accelerated atomic diffusion from P. Simultaneously, increasing the solution treatment temperature allows the small amount of precipitated primary M6C carbides to dissolve in the matrix, while rapid water quenching freezes atomic diffusion, preventing the re-precipitation of M6C carbides during cooling, thus avoiding the reduction of creep fracture strength due to M6C carbides. Additionally, by ensuring that the Nb, Ti, and P contents satisfy (Ti+Nb) / P≤3, the formation of intermetallic phases such as M2P and M3P is reduced, avoiding their impact on creep fracture strength. A higher homogenization treatment temperature is also used to reduce the formation of primary M2P and M3P phases, and the higher solution treatment temperature further prevents the precipitation of M2P and M3P phases.

[0017] 3. On the other hand, the present invention provides a method for preparing the above-mentioned austenitic stainless steel, comprising the following steps: preparing raw materials according to the chemical composition of the austenitic stainless steel, melting and casting the prepared raw materials to obtain a cast billet; then subjecting the cast billet to homogenization treatment, hot working treatment and solution treatment in sequence to obtain the austenitic stainless steel. The solution treatment temperature is 1100~1150℃; the solution treatment holding time is 30~60min. Based on the increase in P content, the solution treatment temperature of this application is higher than the formation temperature of M6C carbides and M2P and M3P phases. Attached Figure Description

[0018] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0019] Figure 1 Metallographic photographs of austenitic stainless steel sheets; wherein: (a) is Example 1; (b) is Example 2; (c) is Example 3; (d) is Comparative Example 1; (e) is Comparative Example 2; (f) is Comparative Example 3; (g, h) is Comparative Example 4; Figure 2 The creep rupture properties of austenitic stainless steel sheet at 550℃; Figure 3 Metallographic images of the creep cavity morphology near the fracture surface after a creep fracture test at 550℃ and 305MPa; where: (a) is Example 1; (b) is Comparative Example 1; (c) is Comparative Example 2; (d) is Comparative Example 3; Figure 4 The images show the morphology of the precipitated phase after a creep rupture test at 550℃ and 305MPa; (a) is Example 1; (b) is Comparative Example 1; (c) is Comparative Example 2; and (d) is Comparative Example 3. Detailed Implementation

[0020] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects according to the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "an embodiment" or "an embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.

[0021] On one hand, the present invention provides an austenitic stainless steel, the chemical composition of which, by weight percentage, is as follows: C≤0.10%, N≤0.12%, Si≤2.0%, Mn:1.0~2.0%, Cr:16.0~18.0%, Ni:10.0~14.0%, Mo:2.0~3.0%, Nb:0.05~0.10%, Ti:0.05~0.10%, S≤0.02%, P:0.04~0.06%, with the balance being Fe and unavoidable residual elements.

[0022] It should be noted that, by increasing the phosphorus (P) content in stainless steel, the interaction between P and vacancies at high temperatures can reduce the diffusion rate of solute atoms such as Cr and Mo, and inhibit the diffusion of M. 23Nucleation of C6 carbides and other compounds at grain boundaries significantly reduced the amount of precipitates, while M... 23 During the coarsening process of C6 carbides, P is expelled outwards, forming P-encapsulated M. 23 The core-shell structure of C6 carbides reduces its coarsening rate, thereby suppressing creep cavities caused by precipitated phases during creep and improving creep fracture strength.

[0023] Because phosphorus (P) readily forms M6C carbides in synergy with elements such as carbon (C) and nitrogen (N), reducing creep rupture strength, to avoid the formation of M6C carbides, in some embodiments, the sum of the mass percentages 'a' of C, N, and P in austenitic stainless steel satisfies the following: a ≤ 0.15%. The mass percentage of C in austenitic stainless steel is ≤ 0.05%. By limiting the content of C+N+P, and further limiting the C content, the carbon source C is reduced, and the increased lattice distortion caused by N and the accelerated atomic diffusion by P are avoided, thereby reducing the formation of M6C carbides. Simultaneously, increasing the solution treatment temperature allows the small amount of precipitated M6C carbides to dissolve in the matrix, while rapid water quenching freezes atomic diffusion, preventing the re-precipitation of M6C carbides during cooling, thus avoiding the reduction of creep rupture strength caused by M6C carbides.

[0024] To obtain a fine-grained microstructure, Nb and Ti are added to refine the grains. However, P readily combines with Nb / Ti to form intermetallic phases such as M2P and M3P, which are detrimental to creep rupture strength. In some embodiments, the sum of the mass percentages of Nb and Ti in austenitic stainless steel is b, and the mass percentage of P is c, where b and c satisfy: b / c ≤ 3. By satisfying the above formula with the content of Nb, Ti, and P, the formation of intermetallic phases such as M2P and M3P is reduced, thus avoiding their impact on creep rupture strength. At the same time, a higher homogenization treatment temperature is used to reduce the formation of primary M2P and M3P phases, and a higher solution treatment temperature is used to prevent the precipitation of M2P and M3P phases.

[0025] At room temperature, the mechanical properties of austenitic stainless steel are: yield strength Rp0.2 ≥ 230 MPa; tensile strength Rm ≥ 540 MPa; elongation A ≥ 50%; impact toughness KV2 ≥ 350 J. At 550℃, the mechanical properties of austenitic stainless steel are: yield strength Rp0.2 ≥ 116 MPa; tensile strength Rm ≥ 396 MPa. At 550℃ for 3000 h, the creep rupture strength of austenitic stainless steel is ≥ 302 MPa. At 550℃ for 10000 h, the creep rupture strength of austenitic stainless steel is ≥ 277 MPa. At 550℃ for 3000 h, the M... 23 The size of C6 carbides is <200 nm.

[0026] On the other hand, the present invention provides a method for preparing any of the above-mentioned austenitic stainless steels, comprising the following steps: The raw materials are prepared according to the chemical composition of austenitic stainless steel, and then melted and cast to obtain a billet. The billet is then subjected to homogenization treatment, heat treatment and solution treatment in sequence to obtain austenitic stainless steel.

[0027] The homogenization treatment temperature is 1230~1250℃; the holding time for homogenization treatment is ≥20h; the solution treatment temperature is 1100~1150℃; the holding time for solution treatment is 30~60min. The hot working process involves forging and rolling of die-cast billets or rolling of continuously cast billets; preferably, the initial rolling temperature after forging is 1100~1200℃, and the final rolling temperature is ≥900℃.

[0028] It should be noted that, traditionally, phosphorus (P) is considered a harmful impurity element, prone to segregation at grain boundaries, reducing grain boundary bonding strength, plasticity, and toughness, especially severely damaging low-temperature performance. This invention first suppresses the driving force of P segregation at its source by employing a higher homogenization treatment temperature, allowing P atoms to obtain sufficient diffusion activation energy and diffuse uniformly from the dendritic segregation zone formed during billet solidification into the matrix, eliminating P micro-enrichment zones and reducing the concentration gradient of P segregation towards grain boundaries during subsequent cooling. Simultaneously, prolonged heat treatment allows for the complete dissolution of coarse carbides in the billet, preventing the synergistic segregation of carbon and P (forming MP). 23C6 exacerbates grain boundary embrittlement; simultaneously, high-temperature homogenization causes the migration and spheroidization of non-equilibrium grain boundaries in the cast billet (such as coarse dendritic grain boundaries formed by casting), reducing the segregation sites of P atoms; at the same time, the primary carbides / inclusions change from a network distribution to a discontinuous spherical distribution, avoiding the initiation of microcracks caused by P enrichment along the inclusion-matrix interface. Hot working treatment breaks down grain boundaries and inhibits the dynamic segregation of P. Among them, the hot working process of billet forging + rolling causes dynamic recrystallization of the cast billet, breaking the coarse cast grains into fine equiaxed grains, greatly increasing the grain boundary area, thereby reducing the P segregation concentration per unit grain boundary area (the total amount of P segregation remains unchanged, but it is dispersed to more grain boundaries, weakening its harmful effect). A final rolling temperature ≥950℃ can prevent deformation within the sensitization temperature range (600~850℃), preventing dynamic segregation of P atoms at deformation-induced grain boundary vacancies. Simultaneously, high-temperature plastic deformation causes grain boundary slippage and migration, disrupting the segregation equilibrium of P atoms and further dispersing the P distribution. Solution treatment and subsequent water quenching freeze the uniform distribution of P and eliminate secondary segregation. The higher solution treatment temperature allows residual trace P-rich phases (such as phosphides) to fully dissolve into the austenite matrix, forming a supersaturated solid solution. Subsequent rapid water quenching (with a cooling rate much greater than the diffusion rate of P atoms) freezes P atoms within the matrix lattice, preventing their diffusion and segregation towards grain boundaries during cooling. Rapid cooling also prevents the precipitation of brittle intermetallic phases such as σ and χ phases, as well as phosphides such as M2P and M3P, during cooling. Furthermore, solution treatment ensures a uniform distribution of alloying elements such as Cr and Ni, preventing the synergistic effect of corrosion and embrittlement caused by Cr depletion at grain boundaries, indirectly improving the material's toughness reserves.

[0029] In another aspect, the present invention provides an application of any of the above-mentioned austenitic stainless steels, which processes the austenitic stainless steels into plates, bars or forgings for fourth-generation nuclear power, thermal power or petrochemical applications, mainly addressing the demand for long-life austenitic stainless steels in harsh working conditions above 500°C in the fields of fourth-generation nuclear power, thermal power or petrochemicals.

[0030] The present invention will be further described below with reference to embodiments and comparative examples.

[0031] Example 1 This embodiment provides a method for preparing a 13mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a phosphorus content of 0.041 wt.%. The specific preparation steps are as follows: 1) Smelting: Weigh the raw materials according to the alloy composition ratio in Table 1, put the prepared raw materials into a 50Kg crucible, smelt them in a vacuum induction furnace, and cast them into ingots. After the ingots have completely solidified, open the mold and take them out.

[0032] 2) Homogenization treatment: Heat the billet to 1240℃ and hold for 24 hours.

[0033] 3) Forging: Heat the ingot to 1150℃, hold for 2 hours, and quickly place it on a hammer forging machine to forge it into a slab. Then air cool it to room temperature. The final forging temperature is above 950℃. The thickness of the forged slab is 40mm.

[0034] 4) Rolling: The forged plate is heated to 1150℃ and held for 2 hours. It is then rolled into a plate on a two-roll hot rolling mill and air-cooled to room temperature. The final rolling temperature is above 950℃ and the thickness of the hot-rolled plate is 13mm.

[0035] 5) Solution treatment: The rolled plate is kept at 1120℃ for 50 minutes and then water quenched to obtain austenitic stainless steel.

[0036] The metallographic structure of the austenitic stainless steel obtained in this embodiment is as follows: Figure 1 As shown in (a). Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 254 MPa, the tensile strength was 596 MPa, the elongation was 72.0%, and the room temperature impact toughness KV2 was 384 J. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. The yield strength Rp0.2 at 550℃ was 129 MPa, and the tensile strength Rm was 442 MPa. Creep rupture performance tests were conducted at 550℃, and creep rupture lives under stresses of 358 MPa, 338 MPa, and 305 MPa were obtained, as shown in Table 3. Figure 2 As shown. Taking 550℃ / 305MPa as an example, the creep rupture life is 2947 h, and the extrapolated creep rupture strength at 550℃ / 10000h is 277MPa. After the 550℃ / 305MPa creep rupture test, the number of creep cavities in the sample is small, and their size is very small, such as... Figure 3 As shown in a, this is because the precipitated phase in the sample is small in size, less than 200 nm, and exhibits a discontinuous distribution, such as... Figure 4 As shown in a.

[0037] Example 2 This embodiment provides a method for preparing a 13mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a phosphorus content of 0.055 wt.%. The sheet production uses the same process parameters as in Example 1.

[0038] The metallographic structure of the austenitic stainless steel obtained in this embodiment is as follows: Figure 1As shown in (b). Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 263 MPa, the tensile strength Rm was 585 MPa, the elongation A was 61.5%, and the room temperature impact toughness KV2 was 382 J. Compared with Example 1, the changes in room temperature yield strength, tensile strength, elongation, and impact toughness were relatively small after increasing the P content. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 2. The yield strength Rp0.2 at 550℃ was 132 MPa, and the tensile strength Rm was 423 MPa. Compared with Example 1, the changes in yield strength and tensile strength at 550℃ were relatively small after increasing the P content. Creep rupture performance tests were conducted at 550℃, and creep rupture lives under stresses of 358 MPa, 338 MPa, and 305 MPa were obtained, as shown in Table 2. Figure 2 As shown. Taking 550℃ / 305MPa as an example, the creep rupture life is 5180 h. Compared with Example 1, the creep rupture life is significantly improved by increasing the P content, with an increase of ~49%.

[0039] Example 3 This embodiment provides a method for preparing a 40mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a phosphorus content of 0.042 wt.%. The specific production process steps for the sheet are as follows: 1) Smelting: Weigh the raw materials according to the alloy composition ratio, smelt them in an electric furnace and cast them into ingots, then electroslag remelt them to prepare electroslag ingots. The ingots should be no less than 5 tons of flat steel ingots.

[0040] 2) Homogenization treatment: Heat the electroslag ingot to 1230℃ and keep it warm for 80 hours.

[0041] 3) Forging: Heat the ingot to 1230℃, hold for 8 hours, and quickly place it on a high-speed forging machine to forge it into a slab. Then air cool it to room temperature. The final forging temperature is above 950℃, and the thickness of the forged slab is ≥180mm.

[0042] 4) Rolling: The forged plate is heated to 1200℃ and held for 6 hours. It is then rolled into a plate on a hot rolling mill and air-cooled to room temperature. The final rolling temperature is above 950℃. The thickness of the hot-rolled plate is 40mm.

[0043] 5) Solution treatment: The rolled sheet is kept at 1130℃ for 50 minutes and then water quenched.

[0044] The metallographic structure of the austenitic stainless steel obtained in this embodiment is as follows: Figure 1(c) shows the results. Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 259 MPa, the tensile strength Rm was 568 MPa, the elongation A was 64.0%, and the room temperature impact toughness KV2 was 371 J. Compared with the 13 mm thick plate of Example 1, the changes in room temperature yield strength, tensile strength, elongation, and impact toughness were relatively small. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. The yield strength Rp0.2 at 550℃ was 137 MPa, and the tensile strength Rm was 433 MPa. Compared with the 13 mm thick plate of Example 1, the changes in yield strength and tensile strength at 550℃ were relatively small. Creep rupture performance tests were conducted at 550℃, and creep rupture lives under stresses of 358 MPa, 338 MPa, and 305 MPa were obtained, as shown in Table 3. Figure 2 As shown. Taking 550℃ / 305MPa as an example, the creep rupture life is 3021 h. This is comparable to the creep rupture life of the 13mm thick plate in Example 1.

[0045] Comparative Example 1 This comparative example provides a method for preparing a 13mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a P content of only 0.004 wt.%. The sheet production uses the same process parameters as in Example 1.

[0046] The metallographic structure of the austenitic stainless steel obtained in this comparative example is as follows: Figure 1 As shown in (d). Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 248 MPa, the tensile strength Rm was 573 MPa, the elongation A was 71.0%, and the room temperature impact toughness KV2 was 386 J. Compared with Example 1, the changes in room temperature yield strength, tensile strength, elongation, and impact toughness were relatively small after reducing the P content. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. The yield strength Rp0.2 at 550℃ was 123 MPa, and the tensile strength Rm was 413 MPa. Compared with Example 1, the changes in yield strength and tensile strength at 550℃ were relatively small after reducing the P content. Creep rupture performance tests were conducted at 550℃, and creep rupture lives under stresses of 358 MPa, 338 MPa, and 305 MPa were obtained, as shown in Table 3. Figure 2 As shown. Taking 550℃ / 305MPa as an example, the creep rupture life was only 698 h. Compared with Example 1, the creep rupture life decreased significantly after the P content was reduced, decreasing by about 76%. After the 550℃ / 305MPa creep rupture test, a certain number of large-sized intergranular cracks were generated in the sample, such as... Figure 3As shown in b, this is due to the formation of large-sized precipitates in the sample, which are continuously distributed at the grain boundaries, such as... Figure 4 As shown in b, the comparison reveals that a decrease in P content significantly increases the tendency for phase precipitation, resulting in noticeable intergranular cracking.

[0047] Comparative Example 2 This comparative example provides a method for preparing a 13mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a P content of 0.058 wt.%, but the C+N+P content is 0.167%, which does not meet the requirement of ≤0.15%. The sheet production uses the same process parameters as in Example 1.

[0048] The metallographic structure of the austenitic stainless steel obtained in this comparative example is as follows: Figure 1 As shown in (e). Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 255 MPa, the tensile strength Rm was 579 MPa, the elongation A was 70.0%, and the room temperature impact toughness KV2 was 376 J. Compared with Example 1, the room temperature yield strength, tensile strength, elongation, and impact toughness showed relatively small changes. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. At 550℃, the yield strength Rp0.2 was 126 MPa, and the tensile strength Rm was 417 MPa. Compared with Example 1, the changes in yield strength and tensile strength at 550℃ were relatively small. Creep rupture performance tests were conducted at 550℃, and the creep rupture life under a stress of 305 MPa was obtained, as shown in Table 3. Figure 2 As shown. Taking 550℃ / 305MPa as an example, the creep rupture life was only 967h. Compared with Example 1, despite having a higher P content (0.058%), the creep rupture life was significantly reduced, decreasing by approximately 67%. After the 550℃ / 305MPa creep rupture test, a certain number of large-sized intergranular cracks were generated in the sample, such as... Figure 3 As shown in (c), this is due to the formation of large-sized precipitates in the sample, which are continuously distributed at the grain boundaries, such as... Figure 4 As shown in (c), the higher C+N+P content significantly increases the tendency for phase precipitation, resulting in obvious intergranular cracking.

[0049] Comparative Example 3 This comparative example provides a method for preparing a 13mm thick austenitic stainless steel sheet. The chemical composition is shown in Table 1, with a P content of 0.042 wt.%, but the (Ti+Nb) / P ratio is 4.05, which does not meet the requirement of ≤3. The sheet production uses the same process parameters as in Example 1.

[0050] The metallographic structure of the austenitic stainless steel obtained in this comparative example is as follows: Figure 1(f) shows the results. Solution-treated plates were subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 249 MPa, the tensile strength Rm was 575 MPa, the elongation A was 59.5%, and the room temperature impact toughness KV2 was 334 J. Compared with Example 1, the room temperature yield strength and tensile strength showed relatively small changes, while the elongation and impact toughness decreased slightly. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. The yield strength Rp0.2 at 550℃ was 128 MPa, and the tensile strength Rm was 410 MPa. Compared with Example 1, the yield strength and tensile strength at 550℃ showed relatively small changes. Creep rupture performance tests were conducted at 550℃, and the creep rupture life under a stress of 305 MPa was obtained. Figure 2 As shown, the creep rupture life was only 586 h. Compared with Example 1, despite having a higher P content (0.042%), the creep rupture life was significantly reduced, decreasing by approximately 80%. After the 550℃ / 305MPa creep rupture test, a certain number of large-sized intergranular cracks were generated in the sample, such as... Figure 3 As shown in (d), this is due to the formation of large-sized precipitates in the sample, which are continuously distributed at the grain boundaries, such as... Figure 4 As shown in (d), the comparison reveals that a higher (Ti+Nb) / P ratio significantly increases the tendency for phase precipitation, resulting in obvious intergranular cracking.

[0051] Comparative Example 4 This comparative example provides a method for preparing a 13mm thick austenitic stainless steel sheet, using the same ingot as in Example 1, and employing the same homogenization treatment, forging, and rolling processes as in Example 1, but with a solution treatment temperature of 1050℃. The specific production process steps for the sheet are as follows: 1) Homogenization treatment: Heat the billet to 1240℃ and hold for 24 hours.

[0052] 2) Forging: Heat the ingot to 1150℃, hold for 2 hours, and quickly place it on a hammer forging machine to forge it into a slab. Then air cool it to room temperature. The final forging temperature is above 950℃. The thickness of the forged slab is 40mm.

[0053] 3) Rolling: The forged plate is heated to 1150℃ and held for 2 hours. It is then rolled into a plate on a two-roll hot rolling mill and air-cooled to room temperature. The final rolling temperature is above 950℃ and the thickness of the hot-rolled plate is 13mm.

[0054] 4) Solution treatment: The rolled plate is kept at 1050℃ for 50 minutes and then water quenched to obtain austenitic stainless steel.

[0055] The metallographic structure of the austenitic stainless steel obtained in this comparative example is as follows: Figure 1As shown in (g), the grains are not uniform, with larger grains of irregular shapes appearing; magnified Figure 1 (h) It can be seen that a certain amount of precipitated phase is distributed within the crystal. The solution-treated plate was subjected to Charpy V-notch impact and tensile property tests at room temperature. The results are shown in Table 2. The room temperature yield strength Rp0.2 was 248 MPa, the tensile strength Rm was 565 MPa, the elongation A was 56.5%, and the room temperature impact toughness KV2 was 304 J. Compared with Example 1, the room temperature yield strength and tensile strength showed relatively small changes, while the elongation and impact toughness decreased. Tensile property tests were conducted at 550℃. The yield strength and tensile strength are shown in Table 3. The yield strength Rp0.2 at 550℃ was 120 MPa, and the tensile strength Rm was 406 MPa. Compared with Example 1, the yield strength and tensile strength at 550℃ showed relatively small changes. Creep fracture performance tests were conducted at 550℃, and the creep fracture life under a stress of 305 MPa was obtained. Figure 2 As shown, the creep rupture lifetime was only 387 h. Compared with Example 1, the creep rupture lifetime was significantly reduced, decreasing by approximately 87%. This comparison demonstrates that a lower solution treatment temperature and the presence of a certain amount of (Ti, Nb) precipitates in the initial solution sample significantly reduce the creep rupture lifetime.

[0056]

[0057]

[0058]

[0059] It will be readily understood by those skilled in the art that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the protection scope of the present invention.

Claims

1. An austenitic stainless steel, characterized in that, The chemical composition of the austenitic stainless steel, by weight percentage, is as follows: C≤0.05%, N≤0.12%, Si≤2.0%, Mn: 1.0~2.0%, Cr: 16.0~18.0%, Ni: 10.0~14.0%, Mo: 2.0~3.0%, Nb: 0.02%, Ti: 0.01%, S≤0.02%, P: 0.04~0.06%, with the balance being Fe and unavoidable residual elements; wherein, the sum of the mass percentages 'a' of C, N, and P in the austenitic stainless steel satisfies: a≤0.15%; The austenitic stainless steel is prepared by a method comprising the following steps: The raw materials are prepared according to the chemical composition of the austenitic stainless steel, and then melted and cast to obtain a billet; then the billet is subjected to homogenization treatment, hot working treatment, solution treatment and water quenching in sequence to obtain the austenitic stainless steel. The solution treatment temperature is 1100~1150℃; the solution treatment holding time is 30~60min. The homogenization treatment temperature is 1230~1250℃; the holding time for the homogenization treatment is ≥20h; The hot working process includes sequential forging and rolling; the initial rolling temperature is 1100~1200℃, and the final rolling temperature is ≥900℃.

2. The austenitic stainless steel according to claim 1, characterized in that, At room temperature, the mechanical properties of the austenitic stainless steel are: yield strength Rp0.2 ≥ 230 MPa; tensile strength Rm ≥ 540 MPa; elongation A ≥ 50%; impact toughness KV2 ≥ 350 J; and / or At 550℃, the mechanical properties of the austenitic stainless steel are: yield strength Rp0.2 ≥ 116 MPa; tensile strength Rm ≥ 396 MPa; and / or Under conditions of 550℃ and 3000h, the creep rupture strength of the austenitic stainless steel is ≥302MPa; and / or Under conditions of 550℃ and 10000h, the creep rupture strength of the austenitic stainless steel is ≥277MPa; and / or Under conditions of 550℃ and 3000h, the M in the austenitic stainless steel 23 The size of C6 carbides is <200 nm.

3. The method for preparing austenitic stainless steel according to any one of claims 1 to 2, characterized in that, Includes the following steps: The raw materials are prepared according to the chemical composition of the austenitic stainless steel, and then melted and cast to obtain a billet; then the billet is subjected to homogenization treatment, hot working treatment, solution treatment and water quenching in sequence to obtain the austenitic stainless steel. The solution treatment temperature is 1100~1150℃; the solution treatment holding time is 30~60min. The homogenization treatment temperature is 1230~1250℃; the holding time for the homogenization treatment is ≥20h; The hot working process includes sequential forging and rolling processes. The initial rolling temperature is 1100~1200℃, and the final rolling temperature is ≥900℃.

4. The application of the austenitic stainless steel according to any one of claims 1 to 2, characterized in that, The austenitic stainless steel is processed into plates, bars or forgings for fourth-generation nuclear power, thermal power or petrochemical applications.

Citation Information

Patent Citations

  • Austenitic stainless steel

    CN101460643A

  • Manufacturing method of high-strength high-corrosion-resistance austenitic stainless steel medium plate

    CN114214564A